1, 4‐Addition of TMSCCl3 to Nitroalkenes: Efficient Reaction Conditions and Mechanistic Understanding. Issue 25 (21st May 2014) - Wu, Na; Wahl, Benoit; Woodward, Simon; Lewis, William
Abstract: Improved synthetic conditions allow preparation of TMSCCl3 in good yield (70 %) and excellent purity. Compounds of the type NBu4 X [X=Ph3 SiF2 (TBAT), F (tetrabutylammonium fluoride, TBAF), OAc, Cl and Br] act as catalytic promoters for 1, 4‐additions to a range of cyclic and acyclic nitroalkenes, in THF at 0–25 °C, typically in moderate to excellent yields (37–95 %). TBAT is the most effective promoter and bromide the least effective. Multinuclear NMR studies ( 1 H, 19 F, 13 C and 29 Si) under anaerobic conditions indicate that addition of TMSCCl3 to TBAT (both 0.13 M ) at −20 °C, in the absence of nitroalkene, leads immediately to mixtures of Me3 SiF, Ph3 SiF and NBu4 CCl3 . The latter is stable to at least 0 °C and does not add nitroalkene from −20 to 0 °C, even after extended periods. Nitroalkene, in the presence of TMSCCl3 (both 0.13 M at −20 °C), when treated with TBAT, leads to immediate formation of the 1, 4‐addition product, suggesting the reaction proceeds via a transient [Me3 Si(alkene)CCl3 ] species, in which (alkene) indicates an Si⋅⋅⋅O coordinated nitroalkene. The anaerobic catalytic chain is propagated through the kinetic nitronate anion resulting from 1, 4 CCl3 − addition to the nitroalkene. This is demonstrated by the fact that isolated NBu4 [CH2 NO2 ] is an efficient promoter. Use of H2 CCH(CH2 )2 CHCHNO2 in air affords radical‐derived bicyclic products arising from aerobic oxidation. Abstract : Understanding TMSCCl3 : The synthesis and reactivity of TMSCCl3 has been investigated. The mechanism of 1, 4‐CCl3 addition to nitroalkenes begins with nitroalkene coordination, followed by the attack of an external fluoride ion, and does not involve the formation of NBu4 [Me3 SiFCCl3 ] (see figure).